Estrategias de enseñanza para desarrollar el pensamiento lógico matemático. - Analuisa Enríquez, Maritza del Rocío (2020)
This research arises from the importance of logical thinking because it is a fundamental axis in the educational task, specifically addresses a problem related to the development of mathematical logical thinking in eighth-year students of the Educational Unit "Jatari Unancha" Guangaje center , from the Pujilí canton, for its solution, the general objective was: To develop teaching strategies to develop mathematical logical thinking. The methodology used has a quantitative approach, combining empirical and theoretical methods, in which the information collection techniques such as the interview and the survey were applied. The first was applied to teachers and the second to students, respectively. The survey focused on Strategies attending to the teaching moment such as pre-instructional, co instructional and post-instructional. Faced with the data collected both in the interview and in the survey, it was evident that there are few activities that are carried out to develop logical thinking in students. This action prompted the development of a proposal framed in strategies for the development of logical thinking in which it includes entertaining activities, which leads students to appropriate knowledge effectively and efficiently, thus conquering students who are autonomous in everything. The teaching-learning process, these strategies were validated with the criteria of experts and users as a feasible alternative for solving the problem, since they are carried out according to the context in which the Institution is found, which represent an active mechanism that unlocks the potentiality in all its representations. Also, students will invigorate the improvement of all their senses.